2008
DOI: 10.1002/hep.22275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk factors for portopulmonary hypertension

Abstract: Portopulmonary hypertension affects up to 6% of patients with advanced liver disease, but the predictors and biologic mechanism for the development of this complication are unknown. We sought to determine the clinical risk factors for portopulmonary hypertension in patients with advanced liver disease. We performed a multicenter case-control study nested within a prospective cohort of patients with portal hypertension recruited from tertiary care centers. Cases had a mean pulmonary artery pressure > 25 mm Hg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
166
0
20

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(206 citation statements)
references
References 26 publications
16
166
0
20
Order By: Relevance
“…Last, although the number of deaths was small, high pulmonary MIF levels were associated with an increased risk of death. Despite significant advances in our knowledge regarding clinical and genetic risk factors for POPH, 11,22 its pathogenesis remains poorly understood. Studies have identified decreased prostacyclin synthase expression, 23 higher serum estradiol levels, and genetic variations in aromatase in patients with POPH, 22 but the mechanistic link between these findings and the pathogenesis of POPH remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Last, although the number of deaths was small, high pulmonary MIF levels were associated with an increased risk of death. Despite significant advances in our knowledge regarding clinical and genetic risk factors for POPH, 11,22 its pathogenesis remains poorly understood. Studies have identified decreased prostacyclin synthase expression, 23 higher serum estradiol levels, and genetic variations in aromatase in patients with POPH, 22 but the mechanistic link between these findings and the pathogenesis of POPH remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications favor the role of cytokines, especially endothelin 1 and interleukin 6. 19 Other studies have demonstrated that sex (females), autoimmune diseases, 20 single-nucleotide polymorphisms of estrogen receptor 1 and phosphodiesterase 5 genes, 21 and other factors 22 were associated with an increased incidence of POPH.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Those results agree with a previous study in which a negative correlation between hepatitis C virus infection and portopulmonary hypertension was shown to exist. 11 Portopulmonary hypertension is usually diagnosed in the fourth or fifth decades of life. 3 Female sex and autoimmune hepatitis are independently associated with portopulmonary hypertension.…”
Section: Epidemiologymentioning
confidence: 99%
“…3 Female sex and autoimmune hepatitis are independently associated with portopulmonary hypertension. 11 In addition, the prevalence and severity of portopulmonary hypertension are not correlated with the severity of liver disease. 4,8,11 The severity of portopulmonary hypertension measured by RHC has also not been found to correlate with the severity of portal hypertension.…”
Section: Epidemiologymentioning
confidence: 99%